Aditivos em dietas de alto fornecimento de grãos para bovinos de corte em confinamento - Belino, Rafael Alves (2011)
The system of constraints has been through technological innovations, using increasingly exploring the potential of livestock in search of more productive use of highly concentrated diets have been more constant, however, the purpose of this study was to evaluate different additives Diets high in grain supply consisting of 85% whole corn grain and 15% of core pellets, the latter composed of 11.55% soybean meal, 0.3% urea and 3.15% of macro and micro minerals and additives. Treatments were: monensin (M), live yeast (LV), virginiamycin (VI) and the combination of monensin, virginiamycin and live yeast (MLVVI). Two experiments were conducted, the first assessed the economic viability and productive performance of 60 Nellore steers, initial weight of 420 kg and age 46 months, in 4 batches of 15 animals in a randomized design (CRD). The experiment lasted 99 days for diets (M) and (MLVVI) and 86 days for diets (VI and LV), where remains were supplied and monitored daily. No significant differences (P> 0.10) for any of the variables such as average daily gain (ADG kg / day), average daily feed intake (CSR kg / day), average feed conversion (FC), carcass hot (WHR%) depending on the experimental diets were respectively averaged 1.15, 7.02, 6.12 and 53.25. In economic evaluation noted remuneration verifying revenue of R$ 0.51, 0.58, 0.14 and 0.17, respectively, for diets M, LV, and VI MLVVI. Scenarios were obtained from the coefficient of variation of some variables, considering the price series from 2007 to 2010 kilos of cattle and 50 kg bag of maize, corrected with the general price index (IGP-DI). Generating six simulations of economic viability for all scenarios, since they are the best, worst, average, more likely, optimistic and pessimistic, respectively obtaining payment of R$ 2.10, -1.43, 0.45, 0, 36, 1.32 and -0.43. In the second experiment evaluated the ruminal eight crossbred European x Zebu steers with ruminal cannulas, initial weight of 590 kg in 4x4 Latin square design replicated (DQL) in individual paddocks. Statistical difference was observed for rumen pH values at time 0, with treatment effect (p = 0.044) later verified by the analysis was significantly higher (p = 0.0605) for the effect of diet (MLVVI vs. VI+LV+M) (p = 0.0346) between diets (LV vs. M) and not significant at the same time for the concentration of ammonia nitrogen N-NH3 (mg / dl) among treatments. There was no difference in mean intakes of DM, CP and nutrients, EE, CT and NDF (kg / d and% BW). There was no treatment effect for NDF (p = 0.0882) and CT (p = 0.0482), showing no statistical significance in any of the variables in orthogonal contrasts. There were differences among diets for the urea nitrogen in plasma PUN (mg / dl) (p = 0.0807) did not show statistical significance for any of the contrasts. The combined use of additives in diets of high grain supply is not possible increases in animal performance.